Gross capital flows as a superior metric in explaning capital flows and allocation in the EU: evidence from 1995-2018 - Toš, Tajana (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2025)
Research on Lucas’s paradox and the allocation puzzle has not reached a consensus on which type of capital should be used to study the magnitude and direction of capital flows. With limited exceptions, the analysis of Lucas’s paradox and the allocation puzzle has predominantly relied on net capital flow variables, as opposed to gross capital inflows and outflows. The frequent inconsistencies in the conclusions of numerous studies may be attributed to variations in variable selection and the lack of precise definition of the chosen variables within the models.The primary objective of this study is to ascertain the appropriate capital flow measure for empirical research of these phenomena. The study was conducted on EU member states and it examined the stability and procyclicality of gross inflows and outflows, as well as net capital flows.The findings strongly suggest that gross capital flow categories should be employed in such analyses, and the conventional reliance on net capital flow variables should be abandoned.
Keywords: net capital flow, gross capital flow, Lucas paradox, allocation puzzle